Lost and found: Rediscovery of the genus Margaromantis Piza, 1982 and consequential nomenclatural changes in the genus Colombiella Koçak & Kemal, 2008 (Mantodea: Mantidae, Photinainae) - Rivera, Julio (Zootaxa, 2010)
Rehn (1916) described Metriomantis planicephala Rehn, 1916 on the basis of one male and one female collected in Cearà Mirim, State of Rio Grande do Norte, Brazil, by the Stanford Expedition to that country in 1911. The new species had several distinct autopomorphies, such as a stout, short, granulated pronotum and a characteristically shaped head, among other unique features. The species remained as a member of Metriomantis but generally was overlooked over the years, even being omitted from Terra’s checklist of Neotropical Mantodea (Terra 1995). Recently, Lombardo (1999) published an important contribution on Metriomantis, which helped to clarify the confusing taxonomic situation of this genus, considered until then as a subgenus of Photina Burmeister, 1838. In the same publication, Lombardo (1999) created a new genus, Rehniella, to accommodate the clearly misplaced M. planicephala. However, the name Rehniella was already in use as it was first created by Hebard (1928) to accommodate a new species of cricket (Rehniella glaphyra Hebard, 1928) from Costa Rica. This case of homonymy was recently detected almost simultaneously by Koçak & Kemal (2008) and Ozdikmen (2008), who independently solved this nomenclatural issue by proposing replacement names for Rehniella Lombardo, 1999: Colombiella, proposed by Koçak & Kemal (2008) and Lombardoa, proposed by Ozdikmen (2008). The name Colombiella was published in May, 2008, whereas Lombardoa was published in June of the same year. Because Colombiella had priority over Lombardoa, Koçak (2008) established the new synonymy.